(A proposed conception to activate the inter-partnership in scientific supervision in the faculties of the human sector at the University of Bisha) - فلاح الشهراني عبد الله; نورين إبراهيم صالح; rabah, ramzi (Journal of College of Education, 2021)
The study aimed to identify the following: the objectives of the inter-partnership for scientific supervision in the faculties of the humanitarian sector at the University of Bisha, the importance of the inter-partnership for scientific supervision in the faculties of the humanitarian sector at the University of Bisha, the disclosure of the culture of faculty members towards the inter-partnership of scientific supervision in the faculties of the humanitarian sector at the University of Bisha, the disclosure On the obstacles to the inter-partnership of scientific supervision in the faculties of the humanitarian sector at the University of Bisha, the study used the descriptive analytical method for its relevance to the nature and objectives of the study. The study reached some results, the most important of which are: the necessity of achieving interaction between faculty members outside the scope of their specializations and faculties, so that inter-partnership programs give scientific supervision; An opportunity for faculty members in various disciplines to meet in the faculties of the humanitarian sector at the University of Bisha - Activating interdisciplinary studies for faculty members specializing in social sciences - Develop procedural solutions to overcome the difficulties of conducting interdisciplinary studies for faculty members specializing in social sciences in a way that contributes to achieving sustainable development In society, activating the role of the inter-partnership for scientific supervision in the faculties of the humanitarian sector at the University of Bisha also requires the following: Establishing research centers based on interdisciplinary research in each of the faculties of the humanitarian sector at the University of Bisha, provided that they have sub-units; To create the means by which the inter-partnership of scientific supervision is activated, and distribute guides and pamphlets to faculty members, to inform them and introduce them to the inter-partnership of scientific supervision and its importance, encourage faculty members to take individual initiatives in upgrading researchers’ ideas, update their expertise, renew their knowledge and skills, and provide Financial incentives to participate in conferences, symposia and scientific societies, dissemination of the culture of inter-partnership for scientific supervision; Through training programs, developing new strategies and approaches to them, focusing on researchers’ performance of their tasks, and encouraging colleges and departments to implement specialized training courses in the inter-partnership of scientific supervision